Exploring the potential of soy by-products: extraction strategies and bioactivity enhancement - Bragagnolo, Felipe S; Santos, Pedro H; Funari, Cristiano S [UNESP]; Rostagno, Maurício A (Elsevier, 2025)
Soybean is a versatile crop, serving as a source of oil, protein, and bioactive compounds. However, the increasing production of soybeans and related products generates significant amounts of by-products, such as straw, hulls, okara, and meal. This review highlights the bioactive compounds present in soy by-products and explores trending methods for their conversion. Our findings reveal that these materials contain significant concentrations of various bioactive compounds, ranging from isoflavones and other flavonoids to peptides. Additionally, the bioactivity of soy by-products can be enhanced through physicochemical, enzymatic, or microbiological treatments, along with improved recovery and accessibility of their bioactive metabolites. Moreover, given the presence of valuable micro- to macro-molecules in soy by-products, a biorefinery approach offers a promising strategy to maximize the recovery of these compounds. Consequently, this approach leads to a framework aligned with the principles of the circular economy and the Sustainable Development Goals.